Новые данные по экологии щитомордника каменистого (Agkistrodon saxatilis) (Reptilia, Crotelidae) в Приморском крае - Коротков, Ю.М. (Вестник зоологии, 1978)
Agkistrodon saxatilis dominates in mountain-forest associations of snakes in Primorye Territory, its occurrence reaches 56.8-84.5%. Most females have a two-year reproductive cycle, some of them — a three-year one. The reproduction potential in populations is equal to 4.8-7.2. After the first wintering about 3.5% of youngsters survive. Adult individuals account for 82-86% of the population number. Populations are located near winter resting-places and are distinguished by ecological and certain morphological characters. The connection between the populations in years of Muridae number depression is maintained by several migrants which could survive in strange wintering places.